Pendidikan Kewarganegaraan dalam Mengatasi Krisis Karakter Pemuda di Era Digital: Analisis Faktor-Faktor yang Mempengaruhi - Sari, Emilia Cahya Febriana; Rambe, Zelda Bintani Putri (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The moral crisis that has plagued us for thousands of years raises deep concerns about the moral values of modern society. The ethical crisis at the turn of the millennium became an increasingly serious and complex problem. Various factors, such as the influence of globalization, technological developments, and social change, shape the context of individual behavior and undermine basic moral values. This essay examines the importance of citizenship education as a key solution for the formation of humanity and social ethics at the turn of the millennium. In today's digital era, citizenship has become an increasingly important part of individual and societal identity. Strengthening citizenship in today's digital era requires citizenship education that is comprehensive and responsive to the challenges of today's digital society. The aim of this brief report is to explain the importance of holistic citizenship education to strengthen citizenship in the digital era and to provide knowledge about how this can be achieved through holistic citizenship education. This research discusses the concept of citizenship education, the role of educational institutions, and the challenges in implementing citizenship values in education. These findings highlight the importance of citizenship education to address the current moral crisis and highlight the need for cooperation between states, educational institutions, and society to achieve this goal.